Implementasi Everyday English Expression Di SMAN 1 Gerung - Sudewi, Ni Ketut Putri Nila; Ramdhani, Suciaty; Syahid, Agus; Miswaty, Titik Ceriyani; Pramanaputra, Abiyyu Alghozy (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2024)
The "Implementation of Everyday English Expression at SMAN 1 Gerung" project aimed to tackle the challenge of enhancing students' practical proficiency in English by integrating everyday language expressions into the educational framework. This initiative responded to the identified gap between formal language instruction and the practical language needs of students, particularly focusing on 10th-grade students at SMAN 1 Gerung, in collaboration with their English language instructors. The methodology involved a structured approach beginning with comprehensive pre-testing to assess baseline competencies, followed by an early evaluation phase to tailor instructional strategies based on identified needs. Orientation sessions were conducted to familiarize participants with the program's objectives and methodologies. The core comprised drilling exercises and continuous feedback, which aimed at reinforcing learning and refining language skills. The service yielded notable outcomes, demonstrating significant improvements in students' spoken proficiency and confidence in utilizing English expressions in everyday contexts. Despite challenges such as resource constraints, the active involvement of educators and the strategic implementation of instructional techniques fostered a conducive learning environment. These program's efficacy in enhancing students' English language proficiency and preparing them for practical language use beyond the classroom.